Interstitial lung disease: retrospective study of the prognostic impact of acute exacerbations - Pacheco, Joana; Santos, Ana Isabel; Catarata, Maria Joana; Freitas, Sara (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: Interstitial lung diseases have high mortality associated with hospitalization for decompensation. There are doubts about the factors involved in the progression of fibrosis, for example the role played by acute exacerbations.  With this work, the authors intend to analyze whether there are predictive parameters of mortality related to exacerbations.Methods: A retrospective study was carried out of patients admitted to the Pulmonology department of Coimbra University Hospital Center for exacerbation of fibrosing lung disease between January 2019 and December 2020. These were classified as: idiopathic pulmonary fibrosis (IPF), fibrosing hypersensivity pneumonitis (FHP) and other fibrosing lung diseases. Statistical analysis was performed using SPSS 26.0 considering statistically significant p